Shoebox Program to Improve The Speech Language Skills of Children with Attention Deficit Hyperactivity Disorder - Misdayani, Misdayani; Hernawati, Tati Hernawati (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
Children with attention deficit and hyperactivity disorders can experience language and speech delays if not treated early. Based on initial observations in the field, it was found that a child with hyperactivity and attention deficit disorder or ADHD aged 3 years and 4 months was late in language development. At that age, children should be able to express desires, ask questions, answer simple questions, respond when called, and be interested in playing with their peers. From an early age, children need to receive intervention as soon as possible from their immediate environment, namely the family, so that children's obstacles can be minimized properly. For this reason, this research aims to develop a program that can improve the language skills of children with ADHD. This program is called Shoebox, which was developed based on the results of an assessment of children's language skills. The program will be implemented by the child's parents through a process of mentoring researchers first until the parents implement it independently. This research uses mixed research methods, namely qualitative research methods as the basis for program development, and quantitative research methods with SSR design to test the program's effectiveness. Data collection techniques are interviews, observation and documentation, and oral language behavior tests. The results of this research are a shoebox program which, based on effectiveness tests, shows that this program can improve speech-language skills in ADHD children.